Improving training in enterprise resource planning systems implementation through communities of practice. (7th December 2012) - Kerr, Don; Burgess, Kevin J.; Houghton, Luke; Murray, Peter A.
The Enterprise Resource Planning (ERP) literature suggests that effective training is one of the key reasons for success in ERP implementations. However, limited research has been conducted on what constitutes effective training in an ERP environment. A case study approach was used to explore the effectiveness of traditional training and to consider if a community based approach could enhance successful training outcomes. There were two major findings. First, the effectiveness of traditional ERP training approaches was limited due to an overreliance on simplistic transmission models and poor appreciation of the role played by organisational context. Second, Communities of Practice (CoPs) allowed ERP implementation training to be more effective through a better dissemination of the training material to the majority of staff who found formal training less effective. This was achieved through the employment of a range of spontaneous strategies including work–a–rounds to overcome perceived weaknesses in the formal information systems.